2014
DOI: 10.1128/aac.01462-13
|View full text |Cite
|
Sign up to set email alerts
|

Efflux Inhibition with Verapamil Potentiates Bedaquiline in Mycobacterium tuberculosis

Abstract: Drug efflux is an important resistance mechanism in Mycobacterium tuberculosis. We found that verapamil, an efflux inhibitor, profoundly decreases the MIC of bedaquiline and clofazimine to M. tuberculosis by 8-to 16-fold. This exquisite susceptibility was noted among drug-susceptible and drug-resistant clinical isolates. Thus, efflux inhibition is an important sensitizer of bedaquiline and clofazimine, and efflux may emerge as a resistance mechanism to these drugs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
105
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 149 publications
(117 citation statements)
references
References 16 publications
11
105
0
1
Order By: Relevance
“…Importantly, all 12 patients who had a post-baseline ⩾4-fold increase in bedaquiline MIC had mutations in Rv0678, a transcriptional repressor of the MmpS5-MmpL5 efflux pump [25]. Recently, this novel efflux mechanism of resistance has been identified to result in low-level resistance to bedaquiline and clofazimine [25,29,30]. The current data do not suggest that increases in bedaquiline MICs due to mutations in Rv0678 have a negative effect on treatment response.…”
Section: Discussionmentioning
confidence: 62%
“…Importantly, all 12 patients who had a post-baseline ⩾4-fold increase in bedaquiline MIC had mutations in Rv0678, a transcriptional repressor of the MmpS5-MmpL5 efflux pump [25]. Recently, this novel efflux mechanism of resistance has been identified to result in low-level resistance to bedaquiline and clofazimine [25,29,30]. The current data do not suggest that increases in bedaquiline MICs due to mutations in Rv0678 have a negative effect on treatment response.…”
Section: Discussionmentioning
confidence: 62%
“…Furthermore, verapamil adjunctive therapy in the rodent model was shown to accelerate bactericidal activity and achieve durable sterilization (10). Moreover, Gupta et al showed that verapamil was able to decrease the MIC of bedaquiline and clofazimine by 8-to 16-fold, which was further confirmed in vivo using a mouse model (11,12).…”
mentioning
confidence: 69%
“…Moxifloxacin was used as a negative control because its activity, as measured in vitro, was previously unaffected by verapamil. Bedaquiline was included as a positive control because the combination of bedaquiline and verapamil showed greater activity against M. tuberculosis in vitro compared with that of bedaquiline alone due to efflux pump inhibition (11). As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…It would be interesting to test whether AcrZ is involved in resistance to the fatty acids and bile salts among the suggested ecological substrates of AcrB, particularly considering that acrZ is regulated by a transcription factor that is sensitive to these compounds (14,15). Studies elucidating the ecologically relevant or endogenous inducers and substrates of efflux pumps will ultimately help us to better understand their evolution, maintenance in diverse genomes, and critical roles in the physiology of pathogens and malignant host cells (58)(59)(60).…”
Section: Discussionmentioning
confidence: 99%